IL-4Rα Polymorphism Is Associated With Myasthenia Gravis in Chinese Han Population - Jiang, Ping; Yue, Yao-Xian; Hong, Yu; Xie, Yanchen; Gao, Xiang; Gu, Chuan-Kai; Hao, Hong-Jun; Qin, Yue; Ding, Xiao-Jun; Song, Min; Li, Hai-Feng; Zhang, Xu (Frontiers in Neurology, 2018)
Interleukin-4 (IL-4) is a potent growth and differentiation factor for B cells which play a vital role in the pathogenesis of myasthenia gravis (MG). IL-4 exerts its function by binding to three types of IL-4 receptor (IL-4R) complexes. IL-4Rα is the key component of the IL-4R complex. We hypothesize that polymorphism of IL-4Rα gene may be associated with the susceptibility and severity of MG. A Chinese cohort of 480 MG patients and 487 healthy controls were recruited. Polymorphisms of IL-4Rα gene were determined with SNPscanTM methods and compared between MG and control groups, as well as among MG subgroups. Rs2107356 and rs1805010 were found to be associated with adult thymoma associated MG, and rs1801275 was found to be associated with adult non-thymoma AChR-Ab positive MG. We did not found association between IL-4Rα polymorphism and the severity of MG. Genetic variations of IL-4Rα were found associated with the susceptibility of MG in Chinese Han population.